(untitled) (THE PRIMARY TEACHER, 2009)
Social and beneficial legislation – Social legislation is designed to protect the interest of a class of society who, because of their economic conditions, deserves such protection. With a view to pass the test of reasonable classification there must exist intelligible differentia between persons or thing grouped together from those who have been left out and there must be a reasonable nexus with the object to be achieved by the legislation. The Court must strive to so interpret the statute as to protect and advance the object and purpose of enactment. Any narrow or technical interpretation of the provisions would defeat the legislative policy. The Court must, therefore, keep the legislative policy in mind in applying the provisions of the Act to the facts of the case.